# Graph y = f(x) and y = x. Then graph y = f -1 (x). f(x) = (x + 1), x = -1

Graph y = f(x) and y = x. Then graph y = f^{-1}(x).

**Transcribed Image Text:**

## f(x) = (x + 1)², x = -1

## This problem has been solved!

Do you need an answer to a question different from the above? Ask your question!

**Related Book For**

## College Algebra With Modeling And Visualization

**ISBN:** 9780134418049

6th Edition

**Authors:** Gary Rockswold

**Question Details**

Chapter #

**5**Section: Exercises 5.2

Problem: 137

## Students also viewed these Mathematics questions